Pemeriksaan Rutin Diabetes Melitus dan Kadar Hidrasi Kulit pada Kelompok Usia Produktif di SMA Santo Yoseph. Cakung - Ni Made Swantari; Alexander Halim Santoso; Daniel Goh; Gracienne Gracienne; Hans Sugiarto; Edwin Destra; Farell Christian Gunaidi (Institut Nalanda, 2025)
Diabetes mellitus is a metabolic disorder characterized by high blood sugar levels resulting from dysfunction in insulin production or action. This disorder not only affects the metabolic system but also impacts skin health, specifically skin hydration, which reflects the skin's ability to maintain optimal moisture levels. Low skin hydration may increase the risk of infections and irritation. This Community Service initiative aims to enhance the understanding and awareness of the productive age group about the importance of routine blood sugar and skin hydration assessments. The method used in this community service activity follows the Plan-Do-Check-Act (PDCA) approach, incorporating education, routine screening, and program effectiveness evaluation. This activity shows that routine check-ups and education play a role in early detection of health risks in the productive age group.